DNMT1 and DNMT3B genetic polymorphisms affect the clinical course and outcome of melanoma patients. Issue 6 (December 2019) - Maric, Helena; Supic, Gordana; Kandolf-Sekulovic, Lidija; Maric, Veljko; Mijuskovic, Zeljko; Radevic, Tatjana; Rajovic, Milica; Magic, Zvonko
Abstract : The aberrant DNA methylation plays a critical role in a number of different malignancies, including melanoma. DNA methylation is catalyzed by DNA methyltransferases ( DNMTs ), involved in methylation maintenance ( DNMT1 ) and de novo DNA methylation ( DNMT3A and DNMT3B ). The current study investigated the association of genetic variants in the DNMT1 and DNMT3B with the clinicopathologic features and the clinical course of melanoma patients. In the present study, DNMT1 (rs2228612, rs2228611, and rs2114724) and DNMT3B (rs406193 and rs2424932) polymorphisms were examined in 123 melanoma patients. Single nucleotide polymorphisms were assessed using TaqMan SNPs Genotyping Assays according to the manufacturer's protocols. The carriers of the variant genotype of DNMT1 rs2228612 had poorer overall survival and recurrence-free survival, ( P = 0.000 and 0.000, respectively), and an increased risk for adverse outcome [hazard ratio (HR) = 6.620, 95% confidence interval (CI): 2.214–19.791, P = 0.001]. DNMT1 rs2228612 was also associated with ulceration ( P = 0.045), nodal status ( P = 0.030), progression ( P = 0. 007), and stage of disease ( P = 0.003). Univariate analysis indicated that tumor-infiltrating lymphocytes could be a marker of good prognosis in melanoma patients (HR = 0.323, 95% CI: 0.127–0.855, P = 0.025), whereas the genotype distribution of the DNMT3B rs406193 polymorphism correlated significantly with the presence of tumor-infiltrating lymphocytes ( P = 0.012). The multivariate analysis showed that the DNMT1 rs2228612 polymorphism (HR = 12.126, 95% CI: 2.345–62.715, P = 0.003) is an independent predictor of poor overall survival in melanoma patients. As expected, disease progression was also found to be an independent prognostic factor in melanoma patients (HR = 37.888, 95% CI: 3.615–397.062, P = 0.002). DNMT1 rs2228612 was found to be an independent predictor of poor overall survival in melanoma patients. DNMTs polymorphisms could serve as a potential target for novel therapeutic approaches.